(untitled) (Biocenosis, 2013)
Bird-keeping as pets is a custom deeply rotted in the Costa Rican culture. One of the most appreciated birds, due to its song, is the Black-faced solitaire. This specie feeds mainly on wild fruits and is founded only in Costa Rica and Panama. Although since 2010 the capture and trade of this specie is prohibited in our country, encaged Black-Faced Solitaires are still common in some communities and the capture of these birds continues, but now illegally. The objective of this study is to know some of the cultural characteristics related to the capture and keeping of the Black-faced solitaire.